Response of Jabuticaba [Plinia cauliflora (Mart) Kausel] seedlings to herbicides - Zimbro, Edna; Bernardi, Caliandra; da Rosa, Viviane; Alamino, Douglas Alvarez; Stefeni, Alberto Ricardo; Wagner Júnior, Américo; Moraes, PedroValério Dutra de (Comunicata Scientiae, 2024)
Jabuticaba (Plinia sp.) is one of the most important fruit species in the Brazilian flora; it is appreciated for fresh consumption or products produced from its fruits. The establishing of orchards requires the determination of management methods that favor the development and productivity of this species. The objective of this work was to evaluate the response of jabuticaba seedlings to application of herbicides and determine possible phytotoxicity. The experiment was conducted at the Federal Technological University of Paraná, in Dois Vizinhos, PR, Brazil. A randomized block experimental design with four replications was used, with 5 plants per experimental unit. The treatments consisted of applications of pre-emergence herbicides (Dual Gold® and Spider®) and post-emergence herbicides (2,4-D, Ally®, Enlist®, Primatop®, Fusilade®, Imazetapyr, Flex®, Plenum®, and Volcane®). The applied herbicide rates were equivalent to 50% of their commercial recommendation. A spray volume equivalent to 250 L ha-1 was applied, using water as diluent. The following parameters were evaluated 45 days after applications: stem diameter at 1 cm above ground (cm); plant height (cm); numbers of necrotic, chlorotic, shriveled, and healthy leaves; number and length of shoots (cm); survival rate (%); and chlorophyll contents (a, b, and total). The application of the herbicides Ally®, Enlist®, and Flex® resulted in less harmful effects on jabuticaba seedlings. The lowest survival rates were found in plants in the treatments with the herbicides Dual Gold®, Volcane®, and Primatop®.